Mobile Devices in Microdrainage Systems in the City of Recife-PE - Santos, Cíntia Rafaela Lima dos; Soares, Willames de Albuquerque (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
The catch basins have paramount importance for an urban drainage system, since its main functionality is to capture and control the volume of transported water from the ground to the existing network, until its arrival in rivers and seas. With disorderly urbanization, the volume of produced garbage grows and drainage systems are impaired. In this way, the present work presents some devices created and implanted in the microdrainage group in the city of Recife. Three eco-basket models were installed inside the collection boxes. The initial version, made of cast iron, did not present a good viability due to its mass, with approximately 30 kg. A second HDPE version was then created, showing positive results, however interactions with some external agents (mainly rodents) reduced its useful life. Finally, the third model was built in fiberglass, meeting expectations satisfactorily. The results obtained proved to be convincing, since that after the implantation of a minimum amount of devices, more than a ton of debris were removed, which would obstruct the microdrainage system, and thus, would potentiate the effects of flooding, still associated with diseases of water transmission and the pollution of urban waters.